Thalamocortical Dysrhythmia: A Theoretical Update in Tinnitus - De Ridder, Dirk; Vanneste, Sven; Langguth, Berthold; Llinas, Rodolfo (Frontiers in Neurology, 2015)
Tinnitus is the perception of a sound in the absence of an external sound source. Pathophysiologically it has been attributed to bottom up deafferentation and/or top down noise-cancelling deficit. Both mechanisms are proposed to alter auditory thalamocortical signal transmission resulting in thalamocortical dysrhythmia (TCD). In deafferentation, TCD is characterized by a slowing down of resting state alpha to theta activity associated with an increase in surrounding gamma activity, resulting in persisting cross-frequency coupling between theta and gamma activity. Theta burst-firing increases network synchrony and recruitment, a mechanism which might enable long range synchrony, which in turn could represent a means for finding the missing thalamocortical information and for gaining access to consciousness. Theta oscillations could function as a carrier wave to integrate the tinnitus related focal auditory gamma activity in a consciousness enabling network, as envisioned by the global workspace model. This model suggests that focal activity in the brain does not reach consciousness, except if the focal activity becomes functionally coupled to a consciousness enabling network, aka the global workspace. In limited deafferentation the missing information can be retrieved from the auditory cortical neighborhood, decreasing surround inhibition, resulting in TCD. When the deafferentation is too wide in bandwidth it is hypothesized that the missing information is retrieved from theta mediated parahippocampal auditory memory. This suggests that based on the amount of deafferentation TCD might change to parahippocampo-cortical persisting and thus pathological theta-gamma rhythm. From a Bayesian point of view, in which the brain is conceived as a prediction machine that updates its memory-based predictions through sensory updating, tinnitus is the result of a prediction error between the predicted and sensed auditory input. The decrease in sensory updating is reflected by decr